2021
DOI: 10.1093/ntr/ntab008
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Content-Based Engagement Patterns in a Smoking Cessation Website and Associations With User Characteristics and Cessation Outcomes: A Sequence and Cluster Analysis

Abstract: Introduction Using WebQuit as a case study, a smoking cessation website grounded in Acceptance and Commitment Therapy, we aimed to identify sequence clusters of content usage and examine their associations with baseline characteristics, change to a key mechanism of action, and smoking cessation. Methods Participants were adult smokers allocated to the WebQuit arm in a randomized controlled trial (n = 1,313). WebQuit contains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…This factorial trial investigates the components of a novel multiple behaviour intervention. While our aim of the trial is to estimate the effects of the components on behaviour, we plan to conduct exploratory studies of engagement, 54 which in combination with effect estimates will be used to determine future directions of study. Decisions to retain or remove components will therefore not be based solely on the statistical analyses in this study, but rather combined with engagement data and the evidence from the literature more widely.…”
Section: Discussionmentioning
confidence: 99%
“…This factorial trial investigates the components of a novel multiple behaviour intervention. While our aim of the trial is to estimate the effects of the components on behaviour, we plan to conduct exploratory studies of engagement, 54 which in combination with effect estimates will be used to determine future directions of study. Decisions to retain or remove components will therefore not be based solely on the statistical analyses in this study, but rather combined with engagement data and the evidence from the literature more widely.…”
Section: Discussionmentioning
confidence: 99%
“…This study contributes to the nascent literature on longitudinal use trajectories of digital health interventions and their prediction of health outcomes [20][21][22][23][24][25]. The study found (1) 1-, 4-, and 26-week trajectories for iCanQuit versus 1-and 3-week trajectories for the QuitGuide smoking cessation apps; (2) that these trajectory groups differentially predicted smoking outcomes at 12 months for iCanQuit but not for QuitGuide; and (3) that certain user characteristics were associated with membership in certain trajectory groups.…”
Section: Principal Findingsmentioning
confidence: 95%
“…Engagement with the assigned app was measured objectively using Google Analytics. The measure of engagement was the number of days each application was opened, which was consistent with other digital interventions' measures of engagement [7,24,25]. For each participant, time-and date-stamped log file records of each page opening were recorded.…”
Section: Engagement: Baseline To Day 182 Log-insmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this line of research is still in its infancy in the field of web-based smoking cessation interventions (c.f., Beatty and Binnion, 2016 ). Only few studies have investigated pre-treatment characteristics as predictors of non-usage attrition in web-based smoking cessation interventions, and they have mainly focused on demographics and smoking-related variables ( Balmford et al, 2008 ; Bricker et al, 2018b ; Cantrell et al, 2016 ; Graham et al, 2006 ; Perski et al, 2021 ; Strecher et al, 2008 ; Wangberg et al, 2008 ). These studies showed that smokers who are younger, male, less educated, less addicted to tobacco, less ready to change, and do not receive other smoking cessation aids (e.g., e-cigarettes or pharmacotherapy) are more likely to stop using web-based smoking cessation interventions.…”
Section: Introductionmentioning
confidence: 99%